Evaluasi Aktivitas Antioksidan Senyawa 4-[(E)-2-(4-okso-3-fenilkuinazolin-2-il)etenil]-benzensulfonamida dan Analognya - Jatmika, Catur; Maggadani, Baitha Palanggatan; Hayun, Hayun (UI Scholars Hub, 2015)
Quinazolinone derivative compounds exhibit a broad spectrum of biological activity, including antioxidant. Quinazolinone derivative compound 4-[(E)-2-(4-oxo-3-phenyl quinazolin-2-yl)ethenyl]-benzensulfonamida and its analogs (2a-f) have been synthesized and demonstrated its activity as a selective inhibitor of cyclooxygenase-2. The aim of this research was to evaluate the antioxidant activity of compound 4-[(E) -2-(4-oxo-3-fenilkuinazolin-2-yl)ethenyl]-benzensulfonamida and its analogs with DPPH radical scavenging method, ferric reducing activity potential (FRAP), and phosphomolybdenum method. The experiment revealed that the % inhibition and antioxidant capacity of compound 2c, 2e and 2f were higher compared to compound 2a, 2b and 2d. The DPPH radical scavenging analysis found that the % inhibition of compound 2c, 2e and 2f at high concentration of compound solution (1000 µg/mL) were 4.8 %, 3.46 %, and 3.68 %, respectively. While the total antioxidant capacity of compound 2c, 2e and 2f were recorded 37.93, 33.4, and 46.3 µg ascorbic acid equivalence/mg of compound, respectively. However the antioxidant activity of all synthesized compounds (2a-f) were lower than the standard ascorbic acid.